2018
DOI: 10.1111/meca.12227
|View full text |Cite
|
Sign up to set email alerts
|

A note on “raising the mandatory retirement age and its effect on long‐run income and Pay As You Go (PAYG) pensions”

Abstract: Fanti (2014, Metroeconomica, 65, 619–645) showed that raising the mandatory retirement age always reduces capital accumulation and may lower per young income and pension benefit, under the assumption that old labor and young labor are perfect substitutes (or equivalently, the elasticity of substitution is infinite). We reexamine his analysis by assuming that the two labors are imperfect substitutes (the elasticity of substitution is finite), and prove that his results no longer hold when the elasticity of subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Lyashok, T.M. Maleva [14] and some foreign authors [15], an older employees show the likely decrease in wages. In our opinion, this trend is already observed: according to Rosstat, the wages of 55-59year-olds and 60-64-year-olds have decreased relatively national average from 100 and 93% in 2005 to 90 and 86% in 2015, respectively.…”
Section: A Possible Economic Negative Consequences (Risks)mentioning
confidence: 95%
“…Lyashok, T.M. Maleva [14] and some foreign authors [15], an older employees show the likely decrease in wages. In our opinion, this trend is already observed: according to Rosstat, the wages of 55-59year-olds and 60-64-year-olds have decreased relatively national average from 100 and 93% in 2005 to 90 and 86% in 2015, respectively.…”
Section: A Possible Economic Negative Consequences (Risks)mentioning
confidence: 95%
“…Fanti [26] showed that under the assumption that the old labor force and the young labor force are complete substitutes (or that the elasticity of substitution is infinite), raising the legal retirement age tends to reduce capital accumulation, and may reduce the young per capital income and pension benefits. Tanaka [27] re-examined the results of Fanti [26] and found that the results of Fanti [26] are only valid when the elasticity of substitution between the old labor force and the young labor force is sufficiently high, otherwise it is not. Kang [28] proposed that postponing retirement and increasing the pension contribution rate will reduce per capital stock, private savings, and young consumption, but postponing retirement can increase old-age consumption, which is better than the policy of increasing social contribution rates.…”
Section: Literature Reviewmentioning
confidence: 99%